2021
DOI: 10.1002/cssc.202101469
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Oxygen Evolution Reaction on Metallocene‐based Transition Metal Sulfides Integrated with N‐doped Carbon Nanostructures

Abstract: In this study, utilizing metallocene and organosulfur chelating agent, an innovative synthetic route was developed towards electrochemically activated transition metal sulfides entrapped in pyridinic nitrogen‐incorporated carbon nanostructures for superior oxygen evolution reaction (OER). Most importantly, the preferential electrochemical activation process, which consisted of both anodic and cathodic pre‐treatment steps, strikingly enhanced OER and long‐lasting cyclic stability. The substantial increase in OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…High-resolution XPS results of N 1s (Figure c) exhibited pyridine N at 398.8 eV, pyrrole N at 400.9 eV, and graphite N at 402.9 eV . Due to sp 2 hybridization, both pyridine N and graphite N in carbon contributed to improving conductivity and surface wettability. As shown in (Figure S11), the chemical states of Co 2p were composed of Co 0 2p 3/2 at 778.2 eV, Co 3+ at 780.5 eV, Co 2+ 2p 3/2 at 782.8 eV, and satellite peak at 786.0 eV. The peak of Co 3+ 2p 3/2 and Co 2+ 2p 3/2 demonstrated the formation of crystal Co 9 S 8 and Co, N-doped carbon hollow polyhedron. The high-resolution spectrograms showed that the peak spacing between W 4f 7/2 and W 4f 5/2 was 2.3 eV, and the peak at 32.4 eV was caused by the W–S bond. The peaks at 162.4 and 163.8 eV were ascribed to S 2p 3/2 and S 2p 1/2 of terminal S 2– and apical S 2– , respectively, , corresponding to WS 2 . The satellite peak (168.6 eV) can be attributed to the partial oxidation of the S atoms on the unsaturated surface to higher oxidation states .…”
Section: Results and Discussionmentioning
confidence: 96%
“…High-resolution XPS results of N 1s (Figure c) exhibited pyridine N at 398.8 eV, pyrrole N at 400.9 eV, and graphite N at 402.9 eV . Due to sp 2 hybridization, both pyridine N and graphite N in carbon contributed to improving conductivity and surface wettability. As shown in (Figure S11), the chemical states of Co 2p were composed of Co 0 2p 3/2 at 778.2 eV, Co 3+ at 780.5 eV, Co 2+ 2p 3/2 at 782.8 eV, and satellite peak at 786.0 eV. The peak of Co 3+ 2p 3/2 and Co 2+ 2p 3/2 demonstrated the formation of crystal Co 9 S 8 and Co, N-doped carbon hollow polyhedron. The high-resolution spectrograms showed that the peak spacing between W 4f 7/2 and W 4f 5/2 was 2.3 eV, and the peak at 32.4 eV was caused by the W–S bond. The peaks at 162.4 and 163.8 eV were ascribed to S 2p 3/2 and S 2p 1/2 of terminal S 2– and apical S 2– , respectively, , corresponding to WS 2 . The satellite peak (168.6 eV) can be attributed to the partial oxidation of the S atoms on the unsaturated surface to higher oxidation states .…”
Section: Results and Discussionmentioning
confidence: 96%
“…Notably, the CMT@MXene provides more catalytically active reaction sites for the OER/ORR with its high surface area of 1300 m 2 g −1 (Figure 4f and Table S1, Supporting Information) resulting in faster diffusion and more O 2 adsorption at the active sites, boosting the reaction kinetics of oxygen electrochemistry. [ 61 ] Co and Mn have high oxidation states, which are suitable for getting high oxygen redox reaction activity and high ligand exchange rate. Furthermore, as the first‐row transition metals, they can be a potential electrocatalyst candidate with greatly boosted electrocatalytic activity, improved electrical conductivity, expedited mass transport, and exposure to large catalytic sites.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the ultra-high OER activity and durability of Ni 5 P 4 /Ni 2 P–FeNi@C can be attributed to the following causes: (1) the in situ formation of NaCl and NaHCO 3 synergistically regulate the pyrolysis process of alkali metal salts and chitosan carbonaceous material [ 40 ]. As a result, the phosphatized product of Ni 5 P 4 /Ni 2 P–FeNi@C encapsulates the Ni 5 P 4 /Ni 2 P heterojunction and FeNi alloy hybrid into a 3D hierarchical porous graphitic carbon framework [ 41 ], which not only provides more active sites and facilitates electron/mass transfer [ 42 ], but also supplies a graphitic carbon protective layer to reduce the corrosion of alloy particles [ 43 ]. (2) Both the NiOOH active layer reconstructed on the surface of Ni 5 P 4 /Ni 2 P and the original FeNi alloy synergistically contribute to the real catalytic active sites.…”
Section: Resultsmentioning
confidence: 99%